From holistic mind to holistic soul: an analytical study of Ibn Rushd’s philosophy - Al-Salahi, Ayad Kareem (International Journal of Psychosocial Rehabilitation, 2020)
Since the theory of any philosopher in the nature of existence as a whole had a clear effect on any issue of his philosophy, it was natural that the nature of the unit in which Ibn Rushd’s philosophy and his own propensity towards (unity of existence), (unity of reason) and (unity of the soul) had a clear effect on many issues of his philosophy; the most prominent of which is in the issue of resurrection of self after leaving body. This opinion was the result of his opinion on the unity of the mind in particular. As far as the unity, universality and the two types of mind is concerned Ibn Rushd says: • A universal active type, that is a substance separate from man, and it is not subject to annihilation and not subject to mixing with matter; but rather is just like the sun from which all minds derive their lights. • An interactive type which is the human mind derived from the active public mind; therefore, it has a constant tendency to contact and join it. Hence, man self is in a constant tendency and a constant yearning for the one.